Challenges and Opportunities of Competing in the Global Market: The Case of Fashion Companies in the Circular Economy Era - Mariana Diah Puspitasari; Lena Ellitan (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The global fashion industry is one of the largest industries in the world, valued at USD 2.5 trillion in 2020. However, it is also one of the largest contributors to greenhouse gas emissions, generating 10% of global emissions and 20% of global wastewater. The circular economy offers new solutions for the fashion industry. This is to address sustainability issues in the fashion industry. The purpose of this study is to analyze good governance practices that can support the transition of fashion companies to a circular economy. In addition, it is able to identify the challenges and opportunities faced by fashion companies in competing in the global market in the circular economy era. It can also develop recommendations for fashion companies on how to achieve governance sustainability and global competitiveness in the circular economy era. This research used a systematic literature review (SLR) approach. The result is that the transition to a circular economy is a great opportunity for companies to increase their profits, competitiveness and reputation. However, this transition also presents some challenges. By applying the right corporate governance principles, identifying opportunities and challenges, and implementing effective strategies, companies can achieve sustainability in the circular economy and contribute to a more sustainable future.